Effect of Eukarion-134 on Akt–mTOR signalling in the rat soleus during 7 days of mechanical unloading - Kuczmarski, J. Matthew; Hord, Jeff M.; Lee, Yang; Guzzoni, Vinicius; Rodriguez, Dinah; Lawler, Matthew S.; Garcia-Villatoro, Erika L.; Holly, Dylan; Ryan, Patrick; Falcon, Kristian; Garcia, Marcela; Janini Gomes, Mariana [UNESP]; et al. (Wiley, 2018)
New Findings: What is the central question of this study? Translocation of nNOSμ initiates catabolic signalling via FoxO3a and skeletal muscle atrophy during mechanical unloading. Recent evidence suggests that unloading-induced muscle atrophy and FoxO3a activation are redox sensitive. Will a mimetic of superoxide dismutase and catalase (i.e. Eukarion-134) also mitigate suppression of the Akt–mTOR pathway? What is the main finding and its importance? Eukarion-134 rescued Akt–mTOR signalling and sarcolemmal nNOSμ, which were linked to protection against the unloading phenotype, muscle fibre atrophy and partial fibre-type shift from slow to fast twitch. The loss of nNOSμ from the sarcolemma appears crucial to Akt phosphorylation and is redox sensitive, although the mechanisms remain unresolved. Abstract: Mechanical unloading stimulates rapid changes in skeletal muscle morphology, characterized by atrophy of muscle fibre cross-sectional area and a partial fibre-type shift from slow to fast twitch. Recent studies revealed that oxidative stress contributes to activation of forkhead box O3a (FoxO3a), proteolytic signalling and unloading-induced muscle atrophy via translocation of the μ-splice variant of neuronal nitric oxide synthase (nNOSμ) and activation of FoxO3a. There is limited understanding of the role of reactive oxygen species in the Akt–mammalian target of rapamycin (mTOR) pathway signalling during unloading. We hypothesized that Eukarion-134 (EUK-134), a mimetic of the antioxidant enzymes superoxide dismutase and catalase, would protect Akt–mTOR signalling in the unloaded rat soleus. Male Fischer 344 rats were separated into the following three study groups: ambulatory control (n = 11); 7 days of hindlimb unloading + saline injections (HU, n = 11); or 7 days of HU + EUK-134; (HU + EUK-134, n = 9). EUK-134 mitigated unloading-induced dephosphorylation of Akt, as well as FoxO3a, in the soleus. Phosphorylation of mTOR in the EUK-treated HU rats was not different from that in control animals. However, EUK-134 did not significantly rescue p70S6K phosphorylation. EUK-134 attenuated translocation of nNOSμ from the membrane to the cytosol, reduced nitration of tyrosine residues and suppressed upregulation of caveolin-3 and dysferlin. EUK-134 ameliorated HU-induced remodelling, atrophy of muscle fibres and the 12% increase in type II myosin heavy chain-positive fibres. Attenuation of the unloaded muscle phenotype was associated with decreased reactive oxygen species, as assessed by ethidium-positive nuclei. We conclude that oxidative stress affects Akt–mTOR signalling in unloaded skeletal muscle. Direct linkage of abrogation of nNOSμ translocation with Akt–mTOR signalling during unloading is the subject of future investigation.
Keywords: Akt; atrophy; hindlimb unloading; mTOR; neuronal nitric oxide synthase; oxidative stress; p70S6K; reactive oxygen species; skeletal muscle